Role of Organizational Culture and Performance of Bumdesa in Improving the Rural Economy - Yuesti, Anik; Castro Menes, Carmen (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 2 (2022): Vol 16 No 2 (2022), 2022)
This study aims to analyze the role of BUMDesaa organizational culture and employees on improving the rural economy, especially for BUMDesaa organizations. In this study, the number of samples used was 102 respondents with the saturated sample method. Methods of collecting data are interviews and questionnaires using a Likert scale, as well as distributing questionnaires using Google Form. The data analysis technique was carried out using Path Analysis (Structural Equation Modeling-Partial Least Square (SEM PLS). The results showed that: Organizational culture positive, Performance, and Job satisfaction have a positive effect on the improvement of the rural economy. Organizational Culture has no effect on job satisfaction, but Performance has a positive effect on job satisfaction. Organizational culture and Performance have a positive effect on improving the rural economy through job satisfaction. Based on these results, it can be explained that organizational culture and performance can improve the rural economy of BUMDesa if employee job satisfaction increases. Increasing employee satisfaction determines the form of organizational culture and performance achievement